Impacts of therapeutic hypothermia on cardiovascular hemodynamics in newborns with hypoxic-ischemic encephalopathy: a case control study using echocardiography. (18th August 2018) - Yoon, Ji Hong; Lee, Eun-jung; Yum, Sook Kyung; Moon, Cheong-jun; Youn, Young-Ah; Kwun, Yoo Jin; Lee, Jae Young; Sung, In Kyung
Abstract: Purpose: The effects of therapeutic hypothermia (TH) on hemodynamics in newborns with hypoxic-ischemic encephalopathy (HIE) were evaluated. Materials and methods: Thirty-two neonates (gestational age, 39.4 ± 1.3 weeks) who had TH for HIE and echocardiographic hemodynamic assessments during TH and post-TH period were studied. Gestational-age-matched 34 healthy neonates were enrolled for comparison. Results: During TH, patients had significantly decreased left ventricular cardiac output (LVCO), descending aorta blood flow (DABF), and DABF/LVCO ratio, and increased resistive index of DA compared to controls. Upper body blood flow (UBBF) remained unchanged but UBBF/LVCO ratio significantly increased during TH. Urine output decreased significantly during TH and increased after rewarming, and showed significant positive correlation with DABF/LVCO ratio. Sixteen patients (50%) showed hypoxic-ischemic (HI) lesions on brain magnetic resonance imaging (MRI) and had significantly increased UBBF/LVCO ratio during TH compared to patients without HI lesions. Patients with UBBF/LVCO ratio >55% had significantly higher risk of having HI lesions on brain MRI (odds ratio 13.0; 95% CI, 2.4–70.2). Conclusions: Decrease in cardiac output and descending aorta blood flow, and preferential cerebral redistribution of cardiac output along with an increase in systemic peripheral vascular resistance may affect systemic organ perfusion and cerebral metabolism.